FACTORS AFFECTING INTEREST INDONESIA MANPOWER OVERSEAS Case Study at PT. Asa noble Virma Yogyakarta - Rusdin, Gimmy; Lastari, SE.,MM., Siswi; N., SE., MM, Winanto (Management, 2010)
The study titled Factors Affecting Interest in Indonesian Workers Abroad This was conducted in August to October of 2008 with the Labor Candidate Indonesian respondents from PT. Asa noble Virma Yogyakarta. This study aims to determine and analyze: (1) whether the Demands of Economic Interest in Candidate influence on Indonesian Workers Abroad?, (2) whether Job Opportunities affect the interests of Candidate Indonesian Manpower Abroad?, (3) whether the Standard Salary affect the interests of Candidate Indonesian Manpower Abroad?. Data collection methods used were interviews and questionnaires. While the methods of data analysis used in this research is quantitative analysis method diskrptif and that is by the method of measurement can be expressed with numbers. Based on the analysis of multiple linear regression equation with t test results can be seen that the demands of Economic Interest in Candidate affect Indonesian Workers Abroad by t count for more than t table (3.804> 2.011). Job Opportunities affect interest Candidate Indonesian Manpower Abroad with t calculate the size of the t table (2.475> 2.011) and to affect the interests of Candidate Salaries Standard Indonesian Workers Abroad by t count for more than t table (4.987> 2.011) . In calculating the F test results also can be seen that the demands of Economy, Employment Opportunities and Salaries Standards jointly affect the interests of Candidate Indonesian Manpower Abroad with calculated F value is greater than F table (24.843> 13.90). Among the variables tested was variable salary standards of the most dominant in influencing Interest Prospective Indonesian Manpower Abroad with beta coefficients of0.306 larger than the demand which has a value of 0.297 Economic and Employment Opportunities with a value of 0.144. Interest Prospective Indonesian Workers Abroad influenced by the demands of Economy, Employment and Salary Standard of 0.786 or equal to 78.6% while 0,21,4 variables influenced others who do not teramasuk in this study. Key words: Factors influence